DEVOLUTION OF POWER TO THE PROVINCES AFTER 18TH CONSTITUTIONAL AMENDMENT IN PAKISTAN: THEORY AND PRACTICE - Saima Naz; Dr. Muhammad Mushtaq; Samaira Khalid; Shamaila Khalid (International Journal of Contemporary Issues in Social Sciences, 2024)
The 18th Constitutional Amendment is a well-known constitutional amendment that contributed significantly towards empowering the provinces through substantial decentralisation. It not only restored the constitution of Pakistan to its original form but also gained the core objectives of devolution of power to the provinces as federal systems exhibit. Both potentials and pitfalls are highlighted through the provision of this amendment to maintain good governance in federating units. 18th Constitutional Amendment is a step forward towards harmonious political and economic union of distribution of resources among the provinces. For the right-size of the federal and provincial governments major fundamental reforms in constitution were needed that could also strengthen the local governments to enforce legislative and citizen-based accountability and implement fiscal discipline. This amendment emphasized on the service delivery performance in all orders of government eliminating provincial barriers that affects mobility and internal trade and restrain the unaccountable governance. It empowered provinces to determine the policies on devolved subjects after abolishing concurrent legislative lists to mitigate the unintended adverse consequence of Eighteenth amendment for nation building in the federation of Pakistan. This amendment is still a hope for cooperative federalism and provincial autonomy at different administrative levels in a global scenario.